2023
DOI: 10.1149/11102.0053ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited, Digital Presentation) Low-Temperature Direct Bonding of Wide-Bandgap Semiconductor Substrates

Abstract: For the next-generation semiconductor devices, our research group has developed direct bonding techniques of wide-bandgap materials, including SiC, Ga2O3, and diamond. It is known that the semiconductor substrates activated by oxygen plasma can form atomic bonds at low temperatures. In this case, a thick oxide layer, which may become a thermal and electrical barrier, is formed at the bonding interface. Meanwhile, our research group demonstrated that the OH-terminated Ga2O3 and diamond substrates were directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The thermal conductivity of the β-Ga 2 O 3 /diamond van der Waals heterogeneous interface has been analyzed in the experiment, which could confirm that the heat dissipation performance of Ga 2 O 3 devices could be significantly improved via the integration of diamond heat sink . It is noteworthy that Matsumae et al achieved the β-Ga 2 O 3 /diamond heterostructure by low-temperature direct bonding of β-Ga 2 O 3 and diamond substrate under atmospheric conditions. , Sittimart et al reported that the electrical performance of diamond/β-Ga 2 O 3 p-n heterojunction diodes fabricated by the interfacial bonding was better than that prepared by van der Waals . In addition, Graham et al reported that the thermal boundary resistance of β-Ga 2 O 3 /diamond heterostructure adhered by van der Waals interactions is 10 times larger than that of interfacial bonding .…”
Section: Introductionmentioning
confidence: 77%
“…The thermal conductivity of the β-Ga 2 O 3 /diamond van der Waals heterogeneous interface has been analyzed in the experiment, which could confirm that the heat dissipation performance of Ga 2 O 3 devices could be significantly improved via the integration of diamond heat sink . It is noteworthy that Matsumae et al achieved the β-Ga 2 O 3 /diamond heterostructure by low-temperature direct bonding of β-Ga 2 O 3 and diamond substrate under atmospheric conditions. , Sittimart et al reported that the electrical performance of diamond/β-Ga 2 O 3 p-n heterojunction diodes fabricated by the interfacial bonding was better than that prepared by van der Waals . In addition, Graham et al reported that the thermal boundary resistance of β-Ga 2 O 3 /diamond heterostructure adhered by van der Waals interactions is 10 times larger than that of interfacial bonding .…”
Section: Introductionmentioning
confidence: 77%
“…However, in addition to self-heating issues, high-temperature working environments can reduce product performance, reliability, and lifespan. Therefore, the reliability of soldering interconnection in SMD packaging of WBG devices has become a focus in the packaging field [1,2] . Recently, TLP has broad application prospects in many fields, and its significant advantages allow it to solve the problem of soldering interconnection [3] .…”
Section: Introductionmentioning
confidence: 99%